Social Downgrading on Consumer Values and Practices: A Transgenerational Perspective - Maria, Mercanti-Guérin (European Journal of Social Science Education and Research, 2023)
The aim of this research is to measure the influence of social downgrading on consumer values and practices. Intergenerational mobility is defined as a process leading to a change in social status from parents to children. The first part of this paper presents social mobility and emphasises its multi-dimensional character. In particular, we detail the different types of objective and subjective mobility. In the second part, we analyse the symbolic and psychological aspects of the acceptance or rejection of social downgrading. We present the results of an exploratory study based on the life stories of a dozen families. It appears that some downgraded individuals do not accept to give up the lifestyle inherited from their childhood and perceive it as an intimate part of their identity. Others, on the contrary, rebuild new identities and modes of consumption based on a "reappropriation of their declassification". This study provides a better understanding of social downgrading by presenting it as a complex process combining the incorporation of a new social status, transgenerational capital and new forms of consumer resistance.
Keywords: Downward Social Mobility, Inter-Generational Mobility, Trans-Generational Capital, Identity, Values, Social Status